2018
DOI: 10.1002/anie.201806922
|View full text |Cite
|
Sign up to set email alerts
|

Nido‐Carboranes: Donors for Thermally Activated Delayed Fluorescence

Abstract: An approach to the design of nido-carborane-based luminescent compounds that can exhibit thermally activated delayed fluorescence (TADF) is proposed. 7,8-Dicarba-nido-undecaboranes (nido-carboranes) having various 8-R groups (R=H, Me, i-Pr, Ph) are appended to the meta or para position of the phenyl ring of the dimesitylphenylborane (PhBMes ) acceptor, forming donor-acceptor compounds (nido-m1-m4 and nido-p1-p4). The bulky 8-R group and meta substitution of the nido-carborane are essential to attain a highly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 67 publications
2
40
0
Order By: Relevance
“…To validate the above calculations, we investigated the photophysical properties of the target compounds (Figure b) in solution in comparison to control compounds ph‐cz and tbu‐cz . Both the bathochromic shift in absorption spectra (see Figure S6) and the evident solvatochromic shift of CT emission (see Figures S7–S9) suggest effective electron coupling between carboranyl and carbazolyl units, consistent with the theoretical calculations (see Figures S28 and S29).…”
Section: Figuresupporting
confidence: 82%
“…To validate the above calculations, we investigated the photophysical properties of the target compounds (Figure b) in solution in comparison to control compounds ph‐cz and tbu‐cz . Both the bathochromic shift in absorption spectra (see Figure S6) and the evident solvatochromic shift of CT emission (see Figures S7–S9) suggest effective electron coupling between carboranyl and carbazolyl units, consistent with the theoretical calculations (see Figures S28 and S29).…”
Section: Figuresupporting
confidence: 82%
“…This distinct HOMO/LUMO separation in the unsymmetrical D-A-A' structures resulted in quite-narrow DE ST values (3 meV for PCZ-CB-TRZ;1 46 meV for TPA-CB-TRZ), whilst the symmetrical D-A-D compound [82] exhibited quite different More recently,L ee, Lee, and co-workersd eveloped unique AIDF-active zwitterionic D-A compounds by employing 7,8-dicarbo-nido-undecarborane( [C 2 B 9 H 10 ] À ), which is an anionic and open-cage analogueo fcloso-carboranes, ast he donor and triarylborane as the acceptor (Figure 13 a). [83] These compounds were readily synthesized by deboration of the corresponding closo-carborane-triarylborane diads by using tetrabutyl ammonium fluoride (TBAF).The absorption spectra of dilutesolutions of nido-mn (n = 1-4) in THF showed as trong absorption at l % 310 nm, which is typical of the p (Mes)!p p (B) CT transition, along with aw eak absorption at l % 350 nm, which was ascribed to an ICT transition from the nido-carborane (D) to the PhBMes 2 moiety (A). Slight red-shifts of the absorption spectra of solutionso fnido-pn (n = 1-4) in THF from those of nido-mn indicated increasede lectronic interactions between the HOMOsa nd LUMOs of the nido-pn compounds.…”
Section: Tadf-a Nd Aie-active (Aidf) Materialsmentioning
confidence: 99%
“…More recently, Lee, Lee, and co‐workers developed unique AIDF‐active zwitterionic D–A compounds by employing 7,8‐dicarbo‐ nido ‐undecarborane ([C 2 B 9 H 10 ] − ), which is an anionic and open‐cage analogue of closo ‐carboranes, as the donor and triarylborane as the acceptor (Figure a) . These compounds were readily synthesized by deboration of the corresponding closo ‐carborane–triarylborane diads by using tetrabutyl ammonium fluoride (TBAF).…”
Section: Multifunctional Emittersmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in various solutions of 2 at higher concentration, the fluorescence emissions vary from 299 to 360 nm upon excitation at 255 nm (Figure 3B and Figure S9), indicating the different photoluminescence mechanism. The intense blue fluorescent emission of compound 1 can be assigned to the local excited-state emission of a Cz-phenylacetylene fragment (Li et al, 2019), and the solvatochromic shift of 2 suggested the intramolecular charge-transfer (ICT) behavior between Cb and Cz units (Wee et al, 2012a; Nghia et al, 2018b). The temperature dependency of emission of 2 was also investigated (Figure S10), the results showed that the fluorescence intensity of 2 slightly decreased when temperature rises, implying that the emission band at around 348 nm was from twisted-ICT state, whose emission effect could be affected by environment conditions such as polarity of solvent and temperature (Nishino et al, 2017).…”
Section: Resultsmentioning
confidence: 99%